INTERROGATING GREEN DISCOURSES IN PATAGONIA-AYSÉN (CHILE): GREEN GRABBING AND ECO-EXTRACTIVISM AS A NEW STRATEGY OF CAPITALISM? - Núñez, Andrés; Benwell, Matthew C.; Aliste, Enrique (Geographical Review)
This paper argues that in Patagonia-Aysén (southern Chile) nature discourses and neoliberalism have a close association. The current discourse of "green" development is presented as a capitalist practice, a renewed form of colonization that creates a narrative around the need to protect this pristine environment because it is a "Reserve of Life." To explore these complex processes further, the paper presents fieldwork undertaken from 2017 to 2019 in the municipalities of Tortel and O'Higgins. Through extensive fieldwork that encompassed interviews and analysis of the Land Registry (Conservadores de Bienes Raíces, or CBR) of the region, we investigated the evolution of private property rights in both municipalities over a period of 29 years (1989–2017) in order to illustrate the changes in land ownership that had occurred. The paper puts forward the concept of eco-extractivism, in order to identify green-grabbing processes undertaken by extractivist investors in Patagonia-Aysén.